An investigation of faculty perspectives on barriers, incentives, and benefits of the OER movement in Turkey - Engin Kursun (Athabasca University Press, 2014)
The purpose of this survey study is to investigate faculty’s perceptions of the main incentives, barriers, and benefits to publishing their course materials for free within the open educational resources (OER) movement. Data were collected from an online survey of 1,637 faculty from 56 universities in Turkey. Results showed that even though the majority of the participants’ perceptions of OER benefits and their attitudes toward publishing their course materials were positive, legal issues were perceived as an obstacle to effective application. Intellectual property protection mechanisms were perceived as the most important incentive to facilitate their contribution.